The Importance of Being Local? Administrative Decentralization and Human Development - Latika Chaudhary; Lakshmi Iyer (Institute of Labor Economics (IZA), 2024)
We examine the human development consequences of transferring responsibility for public service provision to local governments in India, using state-level variation in the timing of administrative decentralization reforms. We find that devolution of the responsibility for health functions from state to local governments, without concomitant authority over personnel or taxation, results in a worsening of neonatal, infant and under-5 child mortality. Such partial devolution results in worse indicators of public health provision, as well as lower rates of primary school completion. Our results cannot be attributed to differential pre-trends, omitted variables bias, or heterogeneous treatment effects.
Keywords: H77; H75; D73; H41; 330; decentralization; infant mortality; primary schooling; local governments; India